Recombinant Human Interleukin-15 and Anti-PD-L1 Combination Therapy Expands a CXCR3+PD1−/low CD8 T-Cell Subset in Simian Immunodeficiency Virus-Infected Rhesus Macaques. (28th September 2019) - Chen, Ping; Chen, Hui; Moussa, Maha; Cheng, Jie; Li, Tong; Qin, Jing; Lifson, Jeffrey D; Sneller, Michael C; Krymskaya, Ludmila; Godin, Steven; Lane, H Clifford; Catalfamo, Marta
Abstract: Background: The PD1/PD-L1 pathway contributes to the pathogenesis of human immunodeficiency virus (HIV)/simian immunodeficiency virus (SIV) infection, and blockade of this pathway may have potential to restore immune function and promote viral control or elimination. In this study, we combined a checkpoint inhibitor anti-PD-L1 (Avelumab) and recombinant human interleukin-15 (rhIL-15) in SIV-infected rhesus macaques (RM). Methods: The rhIL-15 was administered as continuous infusion in 2 cycles of 10 days in the context of weekly administration of anti-PD-L1 (Avelumab) in SIV-infected RM receiving combination antiretroviral therapy (cART). Safety, immunological parameters, and viral loads were monitored during the study. Results: Administration of rhIL-15/anti-PD-L1 was safe and well tolerated. Treatment resulted in transient increases in proliferating (Ki67 + ) natural killer and CD8 T cells. In addition, treatment expanded a CXCR3 + PD1 −/low CD8 T-cell subset with the ability to secrete cytokines. Despite these effects, no changes in plasma viremia were observed after cART interruption. Conclusions: Expansion of the CXCR3 + PD1 −/low CD8 T-cell subset with functional capacity and potential to traffic to sites of viral reservoirs in SIV-infected rhesus macaques had no demonstrable effect on plasma viremia after cART interruption. Abstract : Administration of rIL-15/anti-PD-L1 (Avelumab) in SIV-infected macaques was safe and well tolerated. Although no effects on viremia, treatment promoted expansion of SIV-specific CXCR3 + PD1 −/low CD8 T-cell subset with potential to migrate to sites of viral reservoir and exert effector function.